CHANGES IN THE RELATIONSHIP BETWEEN THE DEGREE OF ENDOTHELIAL FUNCTION DAMAGE AND PLATELET HEMOSTASIS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH INSUFFICIENT COMPENSATION AFTER THE TREATMENT OF HYPERTENSION WITH ANGIOTENSIN II RECEPTOR ANTAGONISTS - Перцева, Н.О. (World of Medicine and Biology, 2014)
Background. Many questions about the relationship between endo-thelial dysfunction and morphological substrate of hemostasis damage that occur during the progress of type 2 diabetes mellitus and arterial hyperten-sion require clarification and further advance. The aim of research. The aim of this study is to determine the rela-tionships between endothelial dysfunction, the degree of renal function dam-age, lipidemic profile and morphological changes of vascular-platelet hemo-stasis in patients with insufficient compensation of type 2 diabetes mellitus and arterial hypertension during 1 year of antihypertensive therapy.Materials and methods. In 87 patients with insufficient glycemic compensation using clinical, laboratory, morphological methods and correla-tional analysis were identified association between endothelial dysfunction, degree of renal function damage, lipidemic profile and morphological chang-es of vascular-platelet hemostasis during 1 year of antihypertensive therapy.Results. It has been established that significant strengthening relation-ships between indicators of endothelial dysfunction and damaged platelet hemostasis formed significant correlations of ultrastructural characteristics of platelets with clinical and laboratory signs of nephropathic and dyslipidemic changes. Elevated levels of endothelial dysfunction markers were in close correlation due to the majority of ultrastructural parameters of vascular-platelet hemostasis. Patients of this contingent greatest strength of reliable linear correlations observed in pairs: endothelin-1 and aggregated platelets (r=+0.83), endothelin-1 and degranulated platelets (r=+0.88), von Willebrand factor and activated platelets (r=+0.79), thrombomodulin and activated platelets (r=+0.81), thrombomodulin and small platelet aggregates (r=+0.79).The indicators of renal function set the following structure correlation with morphological parameters of platelets, observed a direct correlation with the level of albuminuria proportion of activated (r=+0.75; p
Keywords: diabetes mellitus type 2; hypertension; endothelial dysfunction; platelet hemostasis; correlation